(untitled) (Revista Torreón Universitario, 2022)
Introduction and objective: Acute pharyngotonsillitis of bacterial etiology requires antibiotic treatment, the Centor criteria modified by McIsaac are a useful clinical prediction tool to identify patients with bacterial pharyngotonsillitis whose etiology is caused by Group A Streptococcus β-Hemolyticus. The objective of this review was to synthesize the available and accessible medical evidence on the therapeutic efficacy of the Centor criteria modified by MacIsaac and used for the diagnosis and initiation of antibiotic treatment in acute pharyngotonsillitis in children. Methodological design: A systematic review was carried out in the MEDILINE database through the PUBMED meta-search engine, using the following thesauri in the search strategy "preschoolers" AND "Diagnosis" AND "Pharyngitis" OR "tonsillitis". Scientific articles published between 2005-and 2020, without language restriction, with a cross-sectional, cohort, and analytical methodological design were used as inclusion criteria. The following exclusion criteria were used: duplicate studies published outside the study and search period, studies with poor methodological quality after applying the STROBE (STrengthening the Reporting of OBservational studies in Epidemiology) tool. Results: Nine articles were included, which complied with more than ten items contained in the STROBE tool. The evidence included in two studies mentions the importance of using these criteria as a filter to differentiate patients with bacterial pharyngotonsillitis from viral pharyngotonsillitis, emphasizing their usefulness to support antibiotic prescription in patients. Five articles mention that they should be used in a complementary manner with paraclinical tests to confirm the accurate diagnosis of streptococcal infection. Two investigations showed that anamnesis and examination are important for diagnosis, but not sufficient, evidencing that pediatric patients who met three or more criteria have approximately twice the risk of streptococcal infection. Conclusions: The likelihood of having a streptococcal infection increases as the Centor criteria as modified by MacIsaac are met so the clinician should record a thorough oropharyngeal examination in the record to assess the presence or absence of these criteria, which should be supplemented by paraclinical tests for an accurate diagnosis.